2009
DOI: 10.1007/s11999-009-0736-7
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility and Perioperative Complications of Outpatient Knee Arthroplasty

Abstract: The duration of hospitalization and subsequent length of recovery after elective knee arthroplasty have decreased. We hypothesized same-day discharge following either a unicompartmental (UKA) or total knee arthroplasty (TKA) in an unselected group of patients would not result in a higher perioperative complication rate than standardlength hospitalization when following a comprehensive perioperative clinical pathway, including preoperative teaching, regional anesthesia, preemptive oral analgesia, preemptive ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
180
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(186 citation statements)
references
References 16 publications
6
180
0
Order By: Relevance
“…In the USA, THA in an outpatient setting for selected patients has already been described (Berger et al 2009a, Aynardi et al 2014). Moreover, US centers have also reported on hemi- and total knee replacement in an outpatient setting (Berger et al 2009b, Cross and Berger 2014). Although this trend in the USA could well be patient cost-driven, as some patients have to pay extra for each night that they stay in hospital, there does appear to be a general trend towards outpatient joint replacement.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, THA in an outpatient setting for selected patients has already been described (Berger et al 2009a, Aynardi et al 2014). Moreover, US centers have also reported on hemi- and total knee replacement in an outpatient setting (Berger et al 2009b, Cross and Berger 2014). Although this trend in the USA could well be patient cost-driven, as some patients have to pay extra for each night that they stay in hospital, there does appear to be a general trend towards outpatient joint replacement.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent surge of interest in performing THA and TKA in the outpatient setting [3,4,9]. The benefits of outpatient arthroplasty are reported to include higher patient satisfaction and reduced costs [15,29].…”
Section: Introductionmentioning
confidence: 99%
“…This ''observation'' status obscures the division between what is considered inpatient or outpatient. Some studies on outpatient arthroplasty have defined ''outpatient'' status as patients who were discharged the same day [5,9,10], patients who stayed at most one night at the hospital [2,4,24], patients who stayed at most two nights at the hospital [15,25], or simply provided stated status with no quantitative description [16,29,40].…”
Section: Introductionmentioning
confidence: 99%
“…In their retrospective study of 110 patients who underwent OTJA at a center accustomed to rapid rehab protocols and minimally invasive techniques, Berger et al found that inadequate pain control and completing surgery late in the day were most strongly associated with preventing same-day discharge [10]. They found no differences in BMI, average age, body weight, or medical comorbidities between patients who underwent OTJA and those who required inpatient stay [13]. They also found that for patients undergoing TKA, compared to UKA, history of myocardial infarction within 1 year, BMI > 40, and greater than three medical comorbidities were most strongly associated with increased risk of readmission [14].…”
Section: Cautions-identifying Patients Who Are Not Candidates For Otjamentioning
confidence: 99%